Measurement of the γγ*→[eta]c transition form factor - Lees, Jean-Pierre; Adametz, Aleksandra; Marks, Jörg; Schenk, Sebastian; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2010)
We study the reaction e+e−→e+e−ηc, ηc→KSK±π∓ and obtain ηc mass and width values 2982.2±0.4±1.6 MeV/c2 and 31.7±1.2±0.8 MeV, respectively. We find Γ(ηc→γγ)B(ηc→K¯¯¯¯Kπ)=0.374±0.009±0.031 keV, and measure the γγ∗→ηc transition form factor in the momentum transfer range from 2 to 50 GeV2. The analysis is based on 469 fb−1 of integrated luminosity collected at PEP-II with the BABAR detector at e+e− center-of-mass energies near 10.6 GeV.